Outcomes and CT Perfusion Thresholds of Mechanical Thrombectomy for Patients With Large Ischemic Core Lesions - Yang, Hongchao; Lin, Dinglai; Lin, Xiaohui; Wu, Yanmin; Yi, Tingyu; Chen, Wenhuo (Frontiers in Neurology, 2022)
Objective To explore the clinical prognosis and factors after mechanical thrombectomy (MT) in patients with large cerebral infarction assessed by computed tomographic perfusion (CTP)and the optimal threshold of cerebral blood flow (CBF) for estimating ischemic core. Methods We analyzed data from the anterior circulation database of our hospital (August 2018–June 2021). Multivariate logistic regression analyses identified the predictors of clinical outcomes for patients with large baseline infarcts (>50 ml) assessed by the MIStar software. The receiver operating characteristic (ROC) analysis was used to explore the cutoff value of factors. Results The present study included one hundred thirty-seven patients with large baseline infarcts. Moreover, 23 (16.8%) patients achieved functionally independent outcomes, and 50 (36.5%) patients died at 90 days. A total of 20 (14.7%) patients had symptomatic intracranial hemorrhage (sICH). The multivariable analysis showed that higher age and larger core volume were independent of poor outcomes. The cutoff value of core volume was 90 ml, and the age was 76 years. Hypertension and rt-PA treatment were independent factors of sICH. Higher age and larger ischemic volume were independent risk factors of mortality. Conclusions Mechanical thrombectomy can be applied in patients with large ischemic core volumes. Patients older than 76 years with large cores (>90 ml) are unlikely to benefit from MT. These findings may be helpful in selecting patients with large baseline infarcts to be treated by MT. The threshold of CBF < 30% is the independent factor, and this is worth evaluating in future studies to find the optimal threshold of CBF.